Continuous injection direct rolling for optical elements with microstructures. Issue 9 (August 2016) - Wang, Haixiong; Lv, Yonghu; Lou, Yan; Li, Jibin; Cheung, C.
Abstract Continuous injection direct rolling (CIDR) is a new technology used to form optical elements with microstructures. The best process parameters obtained in CIDR are a screw rotational velocity of 160 rpm, an injection temperature of 280 °C, an injection pressure of 12 MPa, a roller rotational velocity of 0.6 rpm, and a roller temperature of 85 °C. Polymer plates with different depth microstructures and a light guide plate (LGP) are produced by CIDR technology. Test results show that the minimum thickness of the plate is 0.621 mm; the roller velocity, roller temperature, and injection pressures all affect the copying of the microstructure; those microstructures on the plate surface were of uniform depth; replication error can be controlled to within 2 %. The LGP obtained from these experiments has good light uniformity, which proved that the technology is feasible for the production of optical elements with microstructure.